2020
DOI: 10.3390/su12020717
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Mitigation: Application of Management Production Philosophies for Energy Saving in Industrial Processes

Abstract: Climate change is a fact. Global warming of the planet is a result of the emission of greenhouse gases into the atmosphere and the cause of serious sustainability issues. The objective of this article is to highlight the potential of the Six Sigma methodology to reduce energy consumption in the productive sphere, with consequential reductions in pollutant emissions. We present a systematic literature review that highlights the increasing interest from academics and practitioners in using quality management phi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…Plant growth promoting rhizobacteria demonstrated a prominent role in plant health improvement and a deliberate greater level of tolerance to various important biotic and abiotic stresses. Global warming is a result of greenhouse gases emission into the atmosphere that cause the serious issues of sustainability [60][61][62]. The isolated best performing bacterial strain was screened to determine its heat tolerance capability and plant growth potential under normal and heat stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Plant growth promoting rhizobacteria demonstrated a prominent role in plant health improvement and a deliberate greater level of tolerance to various important biotic and abiotic stresses. Global warming is a result of greenhouse gases emission into the atmosphere that cause the serious issues of sustainability [60][61][62]. The isolated best performing bacterial strain was screened to determine its heat tolerance capability and plant growth potential under normal and heat stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, mathematical modelling and simulation is also essential as a robust methodological approach. On the other hand, SLR on this subject has also been utilized as a methodology by including green, lean, and six sigma strategies in green-lean, lean six sigma, and green-lean-six sigma combinations [3,19,81,82]. Such an SLR could be deemed as a superset of previous literature work, however, this research study is significant with its distinct characteristic of presenting GLSS as a combined approach in which this strategic combination has been thoroughly examined.…”
Section: Articles Classification By Research Methodologymentioning
confidence: 99%
“…The analysis has indicated that energy reduction, waste reduction, emission reduction, and material and resource conservation are commonly addressed environmental outcomes of GLSS approach. However, other environmental performance measures such as use of environmentally safe material, water eutrophication, environmental compliance, waste disposal, environmental revenues, and water footprint are not frequently addressed due to a lack of research on environmental performance measures [82]. Further, authors have suggested a careful selection of environmental performance measures according to the organizations' and stakeholders' needs, external regulations, and organizational characteristics such as type of the organization, size of the company, industrial sector, and the corporate culture of the organization [79,82].…”
Section: Outcomes Of Glss Approachmentioning
confidence: 99%
“…These schemes can be traditional and well-known, such as lean manufacturing or six-sigma, among others, or simply models developed for each organization [3]. Waste reduction, pollution reductions, improving the efficiency of processes, energy efficiency, emission reductions and others, represent environmental sustainability and social sustainability provides equitable opportunities, encourages diversity, promotes occupational health and safety at work [4][5][6]. These are the three aspects of sustainability according to operational excellence: economic sustainability, environmental sustainability and social sustainability [7].…”
Section: Introductionmentioning
confidence: 99%
“…The term sustainability, from a company's perspective, can be defined as an operations strategy that simultaneously considers the economic, environmental, and social impact of the processes executed by the organization [5,8]. Nowadays, this operations strategy is an important requirement for companies due to established and also emerging environmental concerns, such as increasing consumer preference for environmentally friendly products, inflated energy costs and stricter legislation [6,9,10].…”
Section: Introductionmentioning
confidence: 99%